Hubble Parameter Corrected Interactions in Cosmology - J. Sadeghi; M. Khurshudyan; M. Hakobyan; H. Farahani (Advances in High Energy Physics)
We make steps in a new direction by considering fluids with EoS of more general form F(ρ,P)=0. It is thought that there should be interaction between cosmic fluids, but this assumption for this stage carries only phenomenological character opening a room for different kinds of manipulations. In this paper we will consider a modification of an interaction Q, where we accept that interaction parameter b1 (order of unity) in Q=3Hb1ρ is time dependent and presented as a linear function of Hubble parameter H of the form b0+btH, where b and b0 are constants. We consider two different models including modified Chaplygin gas and polytropic gas which have bulk viscosity. Then, we investigate problem numerically and analyze behavior of different cosmological parameters concerning fluids and behavior of the universe.